Brain glucose uptake is associated with endogenous glucose production in obese patients before and after bariatric surgery and predicts metabolic outcome at follow‐up. Issue 2 (16th September 2018) - Rebelos, Eleni; Immonen, Heidi; Bucci, Marco; Hannukainen, Jarna C.; Nummenmaa, Lauri; Honka, Miikka‐Juhani; Soinio, Minna; Salminen, Paulina; Ferrannini, Ele; Iozzo, Patricia; Nuutila, Pirjo
Abstract : Aims: To investigate further the finding that insulin enhances brain glucose uptake (BGU) in obese but not in lean people by combining BGU with measures of endogenous glucose production (EGP), and to explore the associations between insulin‐stimulated BGU and peripheral markers, such as metabolites and inflammatory markers. Materials and methods: A total of 20 morbidly obese individuals and 12 lean controls were recruited from the larger randomized controlled SLEEVEPASS study. All participants were studied under fasting and euglycaemic hyperinsulinaemic conditions using fluorodeoxyglucose‐positron emission tomography. Obese participants were re‐evaluated 6 months after bariatric surgery and were followed‐up for ~3 years. Results: In obese participants, we found a positive association between BGU and EGP during insulin stimulation. Across all participants, insulin‐stimulated BGU was associated positively with systemic inflammatory markers and plasma levels of leucine and phenylalanine. Six months after bariatric surgery, the obese participants had achieved significant weight loss. Although insulin‐stimulated BGU was decreased postoperatively, the association between BGU and EGP during insulin stimulation persisted. Moreover, high insulin‐stimulated BGU at baseline predicted smaller improvement in fasting plasma glucose at 2 and 3 years of follow‐up. Conclusions: Our findings suggest the presence of a brain‐liver axis in morbidly obese individuals, which persists postoperatively. This axis might contribute to further deterioration of glucose homeostasis.